Case report: Ultrasound-guided bilateral serratus anterior plane block in intensive care unit—An alternative to opioid-sparing postoperative analgesia after sternotomy in infants - Xu, MingZhe; Li, Zhi; He, Yi; Deng, LiJing (Frontiers in Anesthesiology, 2023)
Introduction The high-opioid technique was applied in the setting of congenital cardiac surgery on the belief of severe pain management and analgesic limitation in children along with delayed extubation time and other side effects. Thoracic nerve blockade demonstrated superior postoperative analgesia and stable hemodynamics and lower perioperative opioid consumption and related complications in cardiac surgery. SAPB is a fascial plane block technique that is considered an alternative to paravertebral block for perioperative thoracic pain relief, targeting intercostal never. Cases presentation We present 3 cases to describe the efficacy of SAPB as an alternative to opioid-sparing analgesia performed in infant patients after sternotomy in pediatric cardiac intensive care units. It was successfully used as a part of perioperative pain management. All patients were extubated early and recovered soon with no other complications. Conclusion SAPB lowers perioperative opioid consumption and related complications in cardiac surgery with satisfactory postoperative analgesia and stable hemodynamics.